2014
DOI: 10.1627/jpi.57.251
|View full text |Cite
|
Sign up to set email alerts
|

Supported Metal Hydroxides as Efficient Heterogeneous Catalysts for Green Functional Group Transformations

Abstract: This review article mainly describes our research on the development of highly active heterogeneous catalysts based on the properties of metal hydroxides and efficient green functional group transformations using these catalysts. Metal hydroxide species have both Lewis acid (metal center) and Brønsted base (hydroxy group) sites on the same metal sites. Combined action of the Lewis acid and Brønsted base paired sites can activate various types of organic substrates; for example, alcohols alkoxides, amines amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Comparison of the reaction products derived from 1a (TI-1,10) with those resulting from 4a (TI-3,12) and/or 9a+10a (TI-5,14 + TI- 7,16) shows that 2a, 2c, 6c, 11, 15a, 16a and 20a were derived from 1a only. On the contrary, 9c, 26 and 27 resulted from 4a only.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the reaction products derived from 1a (TI-1,10) with those resulting from 4a (TI-3,12) and/or 9a+10a (TI-5,14 + TI- 7,16) shows that 2a, 2c, 6c, 11, 15a, 16a and 20a were derived from 1a only. On the contrary, 9c, 26 and 27 resulted from 4a only.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…Ruthenium-based catalysts, ruthenium tetraoxide (RuO 4 ) included, have been extensively used to oxidize a wide variety of organic compounds, such as aliphatic and aromatic hydrocarbons, alkenes, alkynes, alcohols, ethers, amines, or amides. [1][2][3][4][5][6][7][8][9][10][11] The versatility, specificity, the high yields obtained in many cases, and the environmentally friendly reaction conditions have strongly recommended ruthenium-containing catalysts be successfully utilized in fine and green chemistry. [1][2][3][4][5][6][7][8][9][10] In the case of tertiary amines of the RCH 2 -NR 1 R 2 type, earlier papers [12][13][14][15][16] indicated that RuO 4 attacks the N-CH 2 positions to afford amides (RCO-NR 1 R 2 ) and for about 30 years, this reaction was viewed as a highly regioselective oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The origin and spectral characteristics ( 1 H-NMR, 13 C-NMR and MS) of compounds 1, 2 and 4-25 (except those of 8f and 14d) were previously presented. imines (2,3) hydroxylamines (4) aldehydes (5) amides I (6, 7), amides II (8) nitrones (9,10) others I (11)(12)(13)(14) nitriles I (15,16), nitriles II (17) cyanoimines (18)(19)(20) cyanonitrones (21,22) formamidines & related compounds (23)(24)(25) others Derivatives 3b, 28 8f, 29 26 30,31 and 27 32 are all known from the literature and were prepared according to the indicated procedures. Compound 28 was purchased from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Several mechanisms for the oxidation of alkanes, 1 arenes, 1 olefins, 2 alcohols 3 and amines [3][4][5][6] using various ruthenium-containing catalysts are known, but they refer to totally different substrates and/or oxidants than those used in the present study. Mechanisms for the oxidation of alkanes, 7,8 alkenes, 9 alcohols, 10 ethers 7 and tertiary amines [11][12][13][14][15] with RuO 4 as an oxidant 16 were previously proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts to synthesize nitriles are being made as these are intermediates in the production of polyamides, pharmaceuticals, dyes and numerous fine chemicals (Fatiadi et al 1983;Miller and Marson 2001). And also, nitrile group serves as an important intermediate in organic synthesis for various functional group transformations (Caddick et al 2000;Munoz et al 2011;Yamaguchi and Mizuno 2014;Wanga 2015) and has often been utilized as a versatile precursor to synthesize various heterocyclic compounds (Aureggi and Sedelmeier 2007;Bosch and Vilarrasa 2007;Nishiwaki et al 2011;Heller et al 2002) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%